The Polish-Russian ‘monument war’ in the context of the Law and Justice’s historical policy - SŁOWIŃSKI, Konrad (Historia i Świat, 2023)
The article addresses the issue of the influence of historical conditions on Polish-Russian relations on the threshold of the 21st century. After the collapse of the communist system in Poland in 1989, the new political elites, guiding the process of democratic transition in the Third Republic of Poland, made efforts to settle the disputed threads of common Polish-Russian history. One of the sources of conflict in terms of the historical burdens was case the removal by Poland of monuments to Red Army soldiers who died on Polish soil. This problem has become an important antagonistic element in bilateral relations, leading to the outbreak of a Polish-Russian 'monument war'. To a large extend, the disputes over Soviet monuments dominated discussions in the Polish-Russian relations, creating another field of conflict on the historical level.